Identifikasi Pemahaman Siswa Terhadap Konsep Ikatan Kimia Pada Siswa Kelas X MIA 3 di SMAN 16 Padang - Santoso, Mugi (RC-INSTITUT, 2019)
Research had done to identify  students's understanding of the concept of chemical bonds at grade X MIA 3 SMAN 16 Padang. This research aims to know the level of understanding of students and cause different levels of students’s understanding based on the way of student learning. Type of this research is descriptive research with qualitative and quantitative approach. The subject of this research were  the whole students of  grade X MIA 3 at SMAN 16 Padang. The subjects were chosen by the technique of Purposive Sumpling, because the highest percentage of incompleteness “not all students could reach learning objective”of students  on the  chemical bonding was on this class. The instruments used during  this research were three-tier multiple diagnostic test and questionnaires. The results showed that 10.01% of students understand the concepts, 49.80% did not understand, 37.86% misconception and 0.48% error. It can be concluded that students' understanding of the chemical bond is categorized as failure.  Because the percentage of students who understand the concept of being under 30%-45%. The cause of the different level of students’s understanding on the  chemical bonds is due to the lack of implementation of indicators repeating subject matter and making schedules and implementation.